2010
DOI: 10.1007/s10165-010-0376-5
|View full text |Cite
|
Sign up to set email alerts
|

Small airway obstruction in patients with rheumatoid arthritis

Abstract: This work was intended to evaluate the prevalence of obstructive small-airway disease in patients with rheumatoid arthritis (RA) and its association with clinical characteristics. Pulmonary function testing (PFT) and high-resolution computed tomography (HRCT) were performed on 189 consecutive RA patients. Each case was diagnosed based on abnormal HRCT findings. We defined obstructive dysfunction of small airways as a forced expiratory flow from 25% to 75% of vital capacity (FEF25–75) value >1.96 residual stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 36 publications
3
27
0
4
Order By: Relevance
“…Middleton et al [12] have reported that, unlike M. tuberculosis, M. avium complex tends to adhere to damaged respiratory mucosa through a fibronectin-mediated process. Recently, we have shown that bronchiolar abnormalities are commonly seen in RA patients, especially those with long-standing RA [13, 14]. In addition, bronchiectasis was the most frequent finding in both patients with early RA and those with long-standing RA [14].…”
Section: Discussionmentioning
confidence: 99%
“…Middleton et al [12] have reported that, unlike M. tuberculosis, M. avium complex tends to adhere to damaged respiratory mucosa through a fibronectin-mediated process. Recently, we have shown that bronchiolar abnormalities are commonly seen in RA patients, especially those with long-standing RA [13, 14]. In addition, bronchiectasis was the most frequent finding in both patients with early RA and those with long-standing RA [14].…”
Section: Discussionmentioning
confidence: 99%
“…A common pathologic mechanism such as circulating immune complexes and complement deposition has been suggested for these multiple organ manifestations of inflammatory process (Mori, Koga, & Sugimoto, 2011). Regarding the role of drug side effect in these diseases, it is necessary to find a multipotential safe medication.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Unexplained pleural or pericardial effusion or thickening on HRCT has been shown to occur more frequently with CTD-ILD than idiopathic interstitial pneumonia. 25 Concomitant airway disease is often present in patients with connective tissue diseases, particularly rheumatoid arthritis 26 , and features such as a disproportionately reduced FEV1 or elevated residual volume on PFTs, mosaic attenuation or bronchiectasis on HRCT or follicular or constrictive bronchiolitis on SLB could be used to make this determination. 19 Pre-capillary pulmonary hypertension is a prevalent clinical manifestation in CTDs, particularly scleroderma 27 , and is defined as a mean pulmonary artery pressure of over 25 mm Hg in the setting of a pulmonary arterial wedge pressure of less than 15 mm.…”
Section: Ipaf Research Statement: the Criteriamentioning
confidence: 99%